Residual activity of 2,4-D amine on soybean plant development - de Oliveira, Elisa Pereira [UNESP]; Kusano, Daniel Makoto; Pacheco, Arthur; Nardelli, Evandro Michel Valero; da Rui, Ricardo Fernando; da Silva, Matheus Gustavo; Teodoro, Paulo Eduardo; da Silva Junior, Carlos Antonio (Science Alert, 2015)
The objective of this research was to evaluate the residual effect of 2,4-D amine on the initial development of soybean plants after its application on the soil at different times before sowing. The experiment was conducted in a greenhouse during the months from April to June 2013, at State University of Mato Grosso do Sul. The experimental design was completely randomized, with four replications. The treatments consisted of eight application times of herbicide 2,4-D amine, seven (3, 6, 9, 12, 15, 18 and 21 days) before sowing, a treatment during sowing (0) and a control treatment (no herbicide application). The dose used was 1080 g i.a. ha-1. It were evaluated he following variables: percentage of emergency, plant height, stem diameter, fresh mass of shoot, fresh mass of roots, dry mass of shoot, dry mass of roots, nodular activity and toxicity. The soybean sowing at time or three days after application of 2,4-D amine causes reduction in the crop development as a result of this residual effect of this herbicide and should occur at least six days after application of this herbicide.
Keywords: Glycine max (L.) Merrill; Herbicide; Toxicity